GPR43 regulates marginal zone B‐cell responses to foreign and endogenous antigens. Issue 2 (28th September 2020) - Rohrbeck, Leona; Adori, Monika; Wang, Shan; He, Chenfei; Tibbitt, Christopher A; Chernyshev, Mark; Sirel, Madle; Ribacke, Ulf; Murrell, Ben; Bohlooly‐Y, Mohammad; Karlsson, Mikael CI; Karlsson Hedestam, Gunilla B; et al.
Abstract: Marginal zone (MZ) B cells are innate‐like B cells that produce polyreactive antibodies with an affinity for microbial molecular patterns and carbohydrate ligands. MZ B cells have been shown to be important in mediating immunity to various bacteria including Streptococcus pneumoniae and are also implicated in inflammatory syndromes including lupus erythematosus. The intestinal microbiota is responsible for producing short‐chain fatty acids, which can regulate immune cell function by several mechanisms including ligation of the G‐protein‐coupled receptor (GPR)43. Herein, we show that MZ B cells express Gpr43 messenger RNA and that the absence of this receptor impacts on MZ B‐cell surface marker expression and antibody production. In T‐cell‐independent responses to the hapten 4‐hydroxy‐3‐nitrophenylacetic acid (NP), mice deficient in GPR43 displayed higher serum titers of NP‐specific antibodies. Moreover, in response to a pneumococcal polysaccharide vaccine, GPR43‐deficient mice developed robust serum antibody responses and had markedly increased numbers of splenic antibody‐secreting cells, compared with control mice. Finally, serum immunoglobulin M autoantibodies to double‐stranded DNA and phosphatidylcholine were increased in resting 10–15‐week‐old mice lacking GPR43. Taken together, mice lacking GPR43 have heightened antibody responses to T‐cell‐independent antigens, which may be a result of impaired regulation of MZ B cells. Abstract : Marginal zone B cells express the short‐chain fatty acid receptor GPR43. Mice lacking GPR43 have heightened responses to T‐cell‐independent antigens and have elevated levels of immunoglobulin M specific for double‐stranded DNA and phosphatidylcholine. Thus, short‐chain fatty acids may regulate marginal zone B‐cell responses to several antigens.